The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5851/kosfa.2021.e64
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, Physical and Sensory Evaluation of Low-Fat Cupuassu Goat Milk Yogurts Supplemented with Fat Replacer

Abstract: Upload this completed form to website with submission ARTICLE INFORMATION Fill in information in each box below Article TypeResearch article Article TitleRheological, physical and sensory evaluation of low-fat cupuassu goat milk yogurts supplemented with fat replacer Running Title (within 10 words)Functional fat replacers to produce low-fat goat milk yogurts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Costa et al . (2022) reported similar results when using whey protein as a fat replacer, increasing from 2.26% to 5.02% from whole milk to skimmed yoghurt added with whey protein. The fat content in RFY and YE treatments was reduced by 89.4% for the former and by 42.9–30.1% for the yoghurts added with emulgel (Table 1).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Costa et al . (2022) reported similar results when using whey protein as a fat replacer, increasing from 2.26% to 5.02% from whole milk to skimmed yoghurt added with whey protein. The fat content in RFY and YE treatments was reduced by 89.4% for the former and by 42.9–30.1% for the yoghurts added with emulgel (Table 1).…”
Section: Resultsmentioning
confidence: 71%
“…The reduction in fat between FFY and RFY contributed to this difference, while variations in protein content in YE treatments were influenced by the presence of WPI in the emulgel and the level of substitution added in RFY to form YE. Costa et al (2022) reported similar results when using whey protein as a fat replacer, increasing from 2.26% to 5.02% from whole milk to skimmed yoghurt added with whey protein. The fat content in RFY and YE treatments was reduced by 89.4% for the former and by 42.9-30.1% for the yoghurts added with emulgel (Table 1).…”
Section: Chemical Compositionmentioning
confidence: 62%
“…However, as this study was a review of previous research within a relatively limited field, concluding that its results represent global research trends in the field of animal agriculture and food may be difficult; hence, continuous monitoring through additional follow-up studies is warranted. [110], [111], [112], [113], [114], [115], [116] Malt Genomic DNA; inflammation; Pediococcus acidilactici; periodontitis; Porphyromonas gingivalis [106] Meat Gut microbiota; meat; protein digestion; proteolytic enzyme; sous-vide [117] Meat products Authentication; essential oils; lipidomics; liquid chromatography-mass spectrometry; low-salt meat products; low-sodium meat products; meat product; metabolomics; nanoemulsion; natural preservative; natural salt replacers; salt alternatives; salt-modifying; salt reduction [118], [119], [120] Meat water-holding capacity; whey; whey protein; whipping cream; whipping property; yogurt [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133],…”
Section: Discussionmentioning
confidence: 99%
“…The probe ran at a rate of 1.0 mm/s before the test, at a rate of 1.0 mm/s during the test, at a rate of 10.0 mm/s after the test, and at a penetration test distance of 25 mm. The data acquisition rate was 400 pps, and the measurement temperature was 15 • C [28].…”
Section: Determination Of Texture (Hardness Consistency and Viscosity...mentioning
confidence: 99%